Acetabular Rim Variants - Richard F. Nauert MD; Robert B. Browning MD; Bryce N. Clinger MD; F. Winston Gwathmey MD (Video Journal of Sports Medicine)
Background and Indications: Acetabular rim ossification variants have a reported incidence of 17%. These variants include labral calcifications, os acetabuli or acetabular rim fractures, and labral ossification. Labral calcifications are small soft calcification deposits within the labrum in patients with femoroacetabular impingement (FAI). The overall cause is unknown. For acetabular rim fractures/os acetabuli, there are several proposed causes, including unfused secondary ossification center (true os acetabuli) and repetitive microtrauma leading to a stress fracture of the acetabulum (acetabular rim fractures). Surgical intervention can include excision versus fixation. Labral ossification involves circumferential ossification of the labrum that is contiguous with the lateral edge of the acetabular rim. Surgical intervention can include labral debridement, repair, or reconstruction. Technique Description: In labral calcification debridement, the superior aspect of the labrum is incised with a radiofrequency device or a beaver blade, and a shaver is reintroduced to remove the calcifications. For acetabular rim fractures/os acetabuli, if excision would lead to iatrogenic dysplasia, then the decision to fix the os back to the acetabulum is made. Several techniques for fixation have been described, including the suture-on-screw technique and the all-suture anchor suture–staple configuration. For labral ossification, surgical decision-making depends on the degree of ossification and the quality of the remaining labrum. If adequate labrum is available, then acetabuloplasty and labral repair are indicated. If inadequate, then acetabuloplasty and labral reconstruction are often chosen. Results: One study reported superior results with excision of the os acetabuli and correction of bony impingement with labral repair compared to FAI alone. A second study demonstrated that patients with labral ossification had significantly lower patient-reported outcomes (PROs) preoperatively but similar improvement postoperatively to patients without labral ossification. Another study showed that patients with symptomatic FAI and labral calcifications can be effectively treated with hip arthroscopy at a 2-year follow-up. Discussion/Conclusion: Acetabular rim ossification variants are common among patients with FAI. The accurate diagnosis and management of these patients are paramount. With appropriate treatment, patients achieve similar improvement in PROs as compared to those with FAI alone. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.